2019
DOI: 10.3390/v11030212
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of an Adjuvanted Middle East Respiratory Syndrome Coronavirus Spike Protein Vaccine in Dromedary Camels and Alpacas

Abstract: MERS-CoV is present in dromedary camels throughout the Middle East and Africa. Dromedary camels are the primary zoonotic reservoir for human infections. Interruption of the zoonotic transmission chain from camels to humans, therefore, may be an effective strategy to control the ongoing MERS-CoV outbreak. Here we show that vaccination with an adjuvanted MERS-CoV Spike protein subunit vaccine confers complete protection from MERS-CoV disease in alpaca and results in reduced and delayed viral shedding in the uppe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
95
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(97 citation statements)
references
References 37 publications
2
95
0
Order By: Relevance
“…It has been shown that a MERS-CoV S1 protein formulated with Ribi (for mice) or aluminum phosphate (for NHPs) adjuvant elicited robust neutralizing antibodies in mice and NHPs against divergent strains of pseudotyped and live MERS-CoV, protecting NHPs from MERS-CoV infection . In addition, MERS-CoV S1 protein adjuvanted with Advax and Sigma Adjuvant System induced low-titer neutralizing antibodies in dromedary camels with reduced and delayed viral shedding after MERS-CoV challenge, but high-titer neutralizing antibodies in alpacas with complete protection of viral shedding from viral infection, indicating that protection of MERS-CoV infection is positively correlated with serum neutralizing antibody titers (Adney et al, 2019). Moreover, immunization with a recombinant MERS-CoV NTD protein (rNTD) can induce neutralizing antibodies and cellmediated responses, protecting Ad-hDPP4-transduced mice against MERS-CoV challenge (Jiaming et al, 2017).…”
Section: Mers-cov Subunit Vaccines Based On Non-rbd S Protein Fragmentsmentioning
confidence: 97%
See 1 more Smart Citation
“…It has been shown that a MERS-CoV S1 protein formulated with Ribi (for mice) or aluminum phosphate (for NHPs) adjuvant elicited robust neutralizing antibodies in mice and NHPs against divergent strains of pseudotyped and live MERS-CoV, protecting NHPs from MERS-CoV infection . In addition, MERS-CoV S1 protein adjuvanted with Advax and Sigma Adjuvant System induced low-titer neutralizing antibodies in dromedary camels with reduced and delayed viral shedding after MERS-CoV challenge, but high-titer neutralizing antibodies in alpacas with complete protection of viral shedding from viral infection, indicating that protection of MERS-CoV infection is positively correlated with serum neutralizing antibody titers (Adney et al, 2019). Moreover, immunization with a recombinant MERS-CoV NTD protein (rNTD) can induce neutralizing antibodies and cellmediated responses, protecting Ad-hDPP4-transduced mice against MERS-CoV challenge (Jiaming et al, 2017).…”
Section: Mers-cov Subunit Vaccines Based On Non-rbd S Protein Fragmentsmentioning
confidence: 97%
“…Therefore, these vaccines may generate potent neutralizing antibodies with strong protective immunity against viral infection. S1 subunit, for example, is much shorter than the full-length S protein, but it is no less able to induce strong immune responses and/or protection against viral infection Adney et al, 2019). Thus, this fragment can be used as an alternative target for subunit vaccine development.…”
Section: Potential Targets For Development Of Sars-cov and Mers-cov Smentioning
confidence: 99%
“…Although it seems that the ultimate origin of MERS-CoV was from bats (6), there are still significant differences between the genome sequences of these betacoronaviruses in bats from the subgenus Merbecovirus and MERS-CoV, suggesting that interspecies jumping from bats to camels may not be a very recent event, and hence the dromedaries are probably the reservoir of MERS-CoV where the virus was transmitted to humans. In the last few years, a number of MERS-CoV vaccines have been developed for their potential use in dromedaries (19)(20)(21)(22)(23). In this study, our results indicated that Bactrian and hybrid camels are also potential sources of MERS-CoV infection.…”
mentioning
confidence: 55%
“…This is likely related to a traditional phenomenon, namely self-limitation or resolution, in which the neutralizing antibodies titer is decreased following the booster immunization as a response to the administrated antigens [24,25]. Several studies showed that the protective efficacy of MERS-CoV vaccines positively correlates with the evoked neutralizing antibody titers in the serum of vaccinated animals [26,27]. These results are in accordance with the results of other viral platforms chimeric viruses carrying spike protein which provided nAbs against MERS-CoV [9,28].…”
Section: Discussionmentioning
confidence: 99%